Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." – Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Black art: A discussion - Araeen, Rasheed; Chambers, Eddie (Third Text, 1988)
Disponible en ligne: https://www.tandfonline.com/doi/abs/10.1080/09528828808576204
Keywords: antiracisme; approches et analyses; arts; asie; cours; discipline; europe; har4610; histoire de l'art; premier cycle; royaume-uni; régions géographiques

Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Section: 239 p. : ill. ; 24 cm
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
http://catalogue.bnf.fr/ark:/12148/cb349656237
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Pandora Press, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. –back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." –From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Section: 99 p.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

Une Histoire des femmes est-elle possible? - Perrot, Michelle (Rivages, 1984)
Les femmes ont-elles une histoire ? Pourquoi cette histoire n’a-t-elle pas été écrite dans le passé et pourquoi se développe-t-elle depuis une dizaine d’années ? De quelles sources dispose-t-on à cet égard et cette démarche implique-t-elle des méthodes particulières ? Que signifient « mémoire », « culture », « pouvoir » des femmes ? La catégorie de sexe est-elle, comme celle des âges, une variable historique issue des nouveaux classements induits par le développement de l’individualisme ? ou quelque chose de plus ? Voilà quelques unes des questions abordées dans ce livre qui prend en compte le changement de direction du regard historique lorsque l’on pose la question du rapport des sexes comme central. Avec la participation d’Alain Corbin, Arlette Farge, Agnès Fine, Catherine Fouquet, Geneviève Fraisse, Christiane Klapisch, Yvonne Knibiehler, Michelle Perrot, Elisabeth Ravoux-Rallo, Jacques Revel, Anne Roche, Pauline Schmitt-Pantel, Sylvie Van de Casteele, Danièle Voldman.
Keywords: arts; cours; discipline; france; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

American women artists, past and present: a selected bibliographic guide - Tufts, Eleanor (Garland Pub, 1984)
Keywords: amériques; arts; bibliographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; régions géographiques; thématiques; états-unis

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Le texte suivant : Owens, Craig. (1983). The Discourse of Others: Feminists and Postmodernism, 57-82 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Section: 64 p. : ill. (certaines en coul.)
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"–
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis